Sex Hormone Binding Globulin (SHBG) Mitigates ER Stress in Hepatocytes In Vitro and Ex Vivo - Katarzyna Kornicka-Garbowska; Lynda Bourebaba; Michael Röcken; Krzysztof Marycz (Cells, 2021)
Despite multiple research studies regarding metabolic syndrome and diabetes, the full picture of their molecular background and pathogenies remains elusive. The latest studies revealed that sex hormone-binding globulin (SHBG)—a serum protein released mainly by the liver—may participate in metabolic dysregulation, as its low serum level correlates with a risk for obesity, metabolic syndrome, and diabetes. Yet, the molecular phenomenon linking SHBG with these disorders remains unclear. In the presented study, we investigate how exogenous SHBG affects metabolically impaired hepatocytes with special attention to endoplasmic reticulum stress (ER stress) and lipid metabolism both in vitro and ex vivo. For that reason, palmitate-treated HepG2 cells and liver tissue samples collected post mortem were cultured in the presence of 50 nM and 100 nM SHBG. We found that SHBG protects against ER stress development and its progression. We have found that SHBG decreased the expression levels of inositol-requiring enzyme 1 (IRE1α), activating transcription factor 6 (ATF6), DNA damage-inducible transcript 3 (CHOP), and immunoglobulin heavy chain-binding protein (BIP). Furthermore, we have shown that it regulates lipolytic gene expression ex vivo. Additionally, herein, we deliver a novel large-animal model to study SHBG in translational research. Our data provide new insights into the cellular and molecular mechanisms by which SHBG modulates hepatocyte metabolism and offer a new experimental approach to study SHBG in human diseases.